Effectiveness of consuming dates in increasing hemoglobin levels in pregnant women with anemia - Nurdin, Nur Aini; Meldawati; Mariana, Frani; Darsono, Putri Vidiasari (Health Sciences International Journal, 2025)
Background: Anemia in pregnancy is a major global health issue, affecting maternal and fetal outcomes. It is often caused by iron deficiency due to increased physiological demands and inadequate nutritional intake. Dietary interventions, including consuming dates (Phoenix dactylifera), are gaining attention as complementary strategies to address this issue. Objective: This study aimed to evaluate the effectiveness of consuming dates in improving hemoglobin levels among pregnant women with anemia. Method: A quasi-experimental study with a one-group pre-test and post-test design was conducted. Twenty-two anemic pregnant women from the Tanjung Aru Public Health Center participated, consuming seven tamr dates (approximately 100 g) daily for 14 days. Hemoglobin levels were measured pre- and post-intervention using the Point of Care Testing (POCT) method. Data were analyzed using paired t-tests to determine statistical significance. Results: Before the intervention, 68.2% of participants had mild anemia, and 31.8% had moderate anemia, with no cases of normal hemoglobin levels. Post-intervention, 45.4% of participants achieved normal hemoglobin levels, while cases of mild and moderate anemia decreased to 36.4% and 18.2%, respectively. The mean hemoglobin level increased significantly from 13.81 g/dL pre-intervention to 14.62 g/dL post-intervention (p = 0.013). Conclusion: Consuming dates effectively improved hemoglobin levels in pregnant women with anemia, offering a promising, culturally appropriate dietary intervention. Further research with larger populations is recommended to validate these findings and explore long-term outcomes.